GRAPHENE-AU FILM SYNTHESIZED FROM GRO IN AU-AQUAEUS SOLUTION AS COUNTER ELECTRODE FOR DSSC APPLICATION - Umar, Marjoni Imamora Ali (Lensa: Jurnal Kependidikan Fisika, 2019)
The study on the optical, electrical properties of multilayer graphene (MLG) obtained by thermal-reduction of graphene oxide (GrO) which was synthesized directly by mixing graphite oxide (GO) flake in 0.005, 0.01, 0.015, and 0.02 M of Au aqueous solution has been successfully performed. The resultant  GrO was subjected to an annealing temperature of 200°C, 400°C, 500°C for 1h to obtain MLG, and G-Au2x, G-Au4x, and G-Au5x (x=.0.005, 0.01, 0.015, and 0.02). The resultant samples were then characterized using FESEM, UV-VIS, four-point probe measurements to study its morphology, optical, and electrical properties. The transmission G-Au increase and its sheet resistant decrease as an increase of annealing temperature. Besides, the annealing treatment was then achieved of its microstructure which is expected may be used as a counter electrode in solar cell applications. The best DSSC devices with Quartz/FTO/ZnO Nanorods/Dye/G-Au50.01/Quartz structures have resulted in current-density, Voc, and solar cell performance of 0.1 mA/cm2, 0.42 V, and 0.01%, respectively.